PENGARUH PRODUKSI KAYU BULAT DAN JUMLAH IPHHK TERHADAP PRODUKSI KAYU GERGAJIAN DI PROVINSI MALUKU - Umi Salam M. Nur; Agus Kastanya; Rohny S. Maail (JURNAL HUTAN PULAU-PULAU KECIL, 2018)
Efforts to increase the utilization of forest products are realized in the form of forest product processing industries which are referred to as primary forest product industries. The total forest area in Maluku Province is 3,919,701 Ha. The potential of natural forest production has decreased significantly. This condition certainly affects the amount of roundwood produced, in other words, the production of round wood has also decreased. On the other hand, the demand for wood in Maluku is very high indicated by the high capacity of existing industries. This condition does not support the sustainability of the timber industry. This research was carried out with the aim of 1) Knowing the production of timber forest products based on a case study conducted in Maluku Province. 2) analyze the effect of sawn timber production and the number of IPHHK on sawn timber production. The result of research show that the number of IPHHK in Maluku Province in 2017 is 80 units of industrial enterprises, the primary of which is active in the process of processing processed wood as much as 57 units. The results of linear regression analysis, it can be seen that because Fcount 7 Ftable, 0.723> 0.457, then H0 is rejected, meaning that there is a significant influence between the amount of round wood production, the number of IPHHK together for sawn timber production.